Keeping the Discussion Among Civil Servants Alive: 'Platform of Values' as an Emerging Genre Within the Public Sector in Sweden - Nyström Höög, Catharina; Björkvall, Anders (Scandinavian Journal of Public Administration, 2018)
A defining feature of contemporary public authorities in Sweden is the production of texts labelled platform of values or core values. Previous research points to three main factors contributing to this development: an increased interest in ethics in the public sector, new forms of management and control, and the importance of the external promotion of public authorities. This paper focuses on the perspective of civil servants when addressing the research question: What are the most important functions of ‘platform of values’ texts? The paper draws on two types of data – a focus group of senior HR officers and a quanti- tative survey for civil servants. Critical Genre Analysis is presented as a methodological framework for understanding ‘value texts’ as social actions. The results show that ‘plat- form of values’ practices are connected to the creation of the “ethically aware” civil servant; that neither their connection to control over civil servants nor to the external promotion of the authority are directly recognised, whereas their connection to goal achievement is; and that the role of the ‘value texts’ as such has been somewhat overrated in previous research – it is the dialogue about the values that matters.